Improve Students Speaking Skill by English Course of Second Grade Student at SMP Negeri 2 Wertamrian - Martinus Itranbey; Pesparani Jabar; Rendy Oratmangun (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
English has an important role in the world. For example, Indonesian use English as their second language after mother tongue. English is also used as one of official language of the United nations. Of fact, we can imagine in that way big the influence of the English language in the current situation. Indonesian government absolutely realizes with this situation. So, they decided English as compulsory subject for formal schooling. In fact, since 2013, the Indonesian has been established as one of local content of the subject in primary schools in the fourth, fifth and sixth. The process of teaching and learning English concentrates on four skills, namely listening, speaking, reading, and writing.